Captopril-induced sialadenitis in a patient with end-stage renal disease - Fatemeh Musavi Mahdiabadi; Naemeh Nikvarz (Wolters Kluwer Medknow Publications, 2016)
Sialadenitis is a rare adverse effect of captopril. We report a case of captopril-induced sialadenitis in a patient with end-stage renal disease (ESRD). A 20-year-old man with ESRD encountered parotid and submandibular swelling after receiving two doses of captopril, administered sublingually. Despite of prescribing dexamethasone, resuming hemodialysis, and discontinuing other drugs that also can cause parotitis, he improved later than what was reported in patients with normal renal function. In conclusion recovery from captopril-induced sialadenitis in patients with ESRD may be more prolonged than that of patients with normal renal function; moreover, early hemodialysis which helps in drug removal may be the most effective treatment.